Pacific farmers enjoy nut boom - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2006)
Farmers in Vanuatu are cashing in on demand for a nut that can be eaten by sufferers of nut allergy...